Cloud based public bus location tracking and notification application for mobile devices - Chee, Xian Yang (2019)
Nowadays, public bus transportation had become more common in Malaysia. However, without a good management system, the bus service might not be fully utilized. Passenger still have to wait for long time under the hot weather for the bus to come and might have higher chances to miss the bus. Therefore, this is a real time bus tracking system developed to solve the problem. An Android based mobile application integrated with Google Map is created to stream the location of public buses in real time and provide estimated arrival time of each buses to the users. Hence, user can go to the bus stop based on the time given instead of waiting at the bus stop under the hot weather. At the same time, the mobile application will be created for the driver to provide their location to the user in real time and a web-based application will be created for the bus company to register their route, manage their driver as well as manage the buses that belong to the company. The whole system will be developed through the RAD cycle and having four phases which is requirement planning, user design, construction and cutover phase. The prototype of system is expected to deliver every loop of the construction phase. They system is aimed to give advantage to the community or people who often using public bus transportation. However, future enhancement to the system is needed to make sure that the phone battery does not drain so fast due to the GPS location service and the current constrain of this system is that it might not benefit to iOS users.